2018
DOI: 10.1123/jpah.2017-0498
|View full text |Cite
|
Sign up to set email alerts
|

Injury Surveillance of Nonprofessional Salsa Dance

Abstract: This is the first study to have described salsa dancers in terms of their injury history profile. Results indicate that the likelihood of sustaining an injury during this physical activity is similar to that of ballroom, but lower than that of Spanish, aerobic, and Zumba®, dance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The search of these dancers for activities that complemented their training routine was evidence of their professional dedication to the modality of dancing, just as high yield sport requires the development of advanced technical knowledge and the improvement of specific abilities at high demand levels 18 . This fact has been reported in the li-terature as a potential cause of the development of injuries in the different dance modalities 1,2,5,6 .From the results obtained in the present study, it was possible to verify that the expected hypothesis was confirmed in parts since the presence of lesion was found in more than half of the sample. However, although individuals of both sexes presented some type of lesion injury, there was no gender disparity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The search of these dancers for activities that complemented their training routine was evidence of their professional dedication to the modality of dancing, just as high yield sport requires the development of advanced technical knowledge and the improvement of specific abilities at high demand levels 18 . This fact has been reported in the li-terature as a potential cause of the development of injuries in the different dance modalities 1,2,5,6 .From the results obtained in the present study, it was possible to verify that the expected hypothesis was confirmed in parts since the presence of lesion was found in more than half of the sample. However, although individuals of both sexes presented some type of lesion injury, there was no gender disparity.…”
Section: Discussionsupporting
confidence: 81%
“…Another risk factor that demonstrated a greater chance ratio for the occurrence of injuries in the present study was the weight status, independent of sex. Some studies carried out in the area of professional dancing, generally with classical ballet, portrayed male dancers as eutrophic individuals and commonly within the range of normality 6 . Nevertheless, the sample investigated identified professional dancers, both male and female, who were overweight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations